Numerical study of coal dust behaviours and experimental investigation on coal dust suppression efficiency of surfactant solution by using wind tunnel tests - Chang, Ping; Chen, Y.; Xu, G.; Huang, J.; Ghosh, Apurna; Liu, W.V. (TAYLOR & FRANCIS INC, 2019)
Coal dust is one of the most serious hazards on mine sites. Water spray with surfactant added is an effective way to control the coal dust. In this study, wind tunnel experiments were designed to evaluate the surfactant on coal dust suppression efficiency. A CFD modeling was first constructed in to investigate the coal dust particles movement characteristics, and the stimulation results were provided for the wind tunnel design. The CFD results indicated that the location of the nozzle placement and the time for the water spraying start time. The coal dust suppression efficiency was then evaluated in the presence of different surfactants. The experiment results suggest that the anionic and non-ionic surfactants are helpful to improve the suppression efficiency while the cationic surfactant failed to increase it. For the SDBS at various concentrations, the highest suppression efficiency is achieved when at 0.20%. Compared with the larger coal dust particles, the finer ones are more difficult to capture for both water and SDBS surfactant solution. The results also demonstrate the potential application of this surfactant on coal mine industries.